Double Trouble: Gender Fluid Heroism in American Children’s Television - Lamari Lou (De Gruyter, 2021)
Gender fluidity makes only rare appearances on North American television, and remains almost completely absent from programming for children. In contrast, transgender characters are making inroads into mainstream North American TV for adults. Still, media depictions of transgender people in the late 1990s and early 2000s have largely shown them as aberrations, having illegible and/or unstable identities, joining mainstream Euro North American society which tends to medicalize and pathologize transgender identities. Thus, too often the representation provided serves only to reinforce binaries by making the character exceptional and noting their unconventionality, or to highlight gender fluidity as a problem. Examining the animated streaming TV series She-Ra and the Princesses of Power (2018–2020), we use scholarship on gender fluidity to critique the show’s representations of genders in addition to and beyond male and female. Looking at She-Ra through this lens, the show challenges assumptions about princesses, villains, helpers, and heroes. Ultimately transgressing traditional categories, the princesses and their allies, in their own distinct embodiments and self-presentations, use their differing magical and other skills to fight enemies in the Evil Horde to protect their planet, Etheria.